Participant Observation: Embodied Insights, Challenges, Best Practices and Looking to the Future - Nabhan-Warren, Kristy ca. 20./21. Jh. (Fieldwork in religion, 2022)
This article reflects on the method of participant observation (PO) and how the author has interpreted and practiced it throughout her career as an anthropologist of religion. The article concentrates on the embodied insights afforded by PO, as well as the physical, existential and ontological challenges of the PO method. The author shares examples from her own PO experiences and recommends best practices as well as some ideas for improvement. The challenges of conducting PO during an ongoing pandemic, and some lessons that may have been learned, are considered. The article ends with a brief reflection on the future of participation observation and what the pandemic has taught about what it means to be anthropologists.